2015
DOI: 10.1152/ajpheart.00693.2014
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of cystathionine β-synthase into RVLM increases hydrogen sulfide-mediated suppression of sympathetic outflow via KATP channel in normotensive rats

Abstract: transfer of cystathionine ␤-synthase into RVLM increases hydrogen sulfide-mediated suppression of sympathetic outflow via KATP channel in normotensive rats. Am J Physiol Heart Circ Physiol 308: H603-H611, 2015. First published January 16, 2015; doi:10.1152/ajpheart.00693.2014.-Hydrogen sulfide has been shown to have a sympathoinhibitory effect in the rostral ventrolateral medulla (RVLM). The present study examined the function of cystathionine ␤-synthase (CBS)/hydrogen sulfide system in the RVLM, which plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…One way or the other, these depolarizing effects seem to be followed by longer latency hyperpolarizations that results from the activation of KATP channels, that have been suggested to be involved not only in the blood pressure regulation (Foster and Coetzee, 2016) but also in pulmonary ventilation, i.e., systems controlled by the NTS. Another putative region potentially affected by AOA is the rostral ventrolateral medulla (RVLM) where an increased KATP channels activity has been suggested to be responsible for a greater sympathetic outflow and pressor effect (Duan et al, 2015). We speculate that the fairly different (accentuated) effects of H2S on respiration and cardiovascular function during hypoxia in SHR may result from the activation of KATP channels in structures of the brain stem by H2S.…”
Section: Discussionmentioning
confidence: 91%
“…One way or the other, these depolarizing effects seem to be followed by longer latency hyperpolarizations that results from the activation of KATP channels, that have been suggested to be involved not only in the blood pressure regulation (Foster and Coetzee, 2016) but also in pulmonary ventilation, i.e., systems controlled by the NTS. Another putative region potentially affected by AOA is the rostral ventrolateral medulla (RVLM) where an increased KATP channels activity has been suggested to be responsible for a greater sympathetic outflow and pressor effect (Duan et al, 2015). We speculate that the fairly different (accentuated) effects of H2S on respiration and cardiovascular function during hypoxia in SHR may result from the activation of KATP channels in structures of the brain stem by H2S.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, we found in the W-S group a depletion of Peptococcaceae , a sulfate-reducing bacteria considered to be beneficial in the regulation of BP (Ahmad et al, 2012; Yu et al, 2018). Sulfate-reducing bacteria, and hydrogen sulfide released in the colon may also contribute to the control of arterial BP, being antihypertensive, at least in part, through suppression of sympathetic outflow (Duan et al, 2015). The genus Blautia , which is the main bacterial group in Clostridium coccoides-group, was also found to decrease in Japanese patients with type 2 diabetes, as compared with control subjects (Sato et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigations revealed that H 2 S facilitates baroreflexive sensitivity in normal rats by acting on the baroreceptor (Xiao et al, 2006 ; Guo et al, 2016 ) or the rostral ventrolateral medulla (Guo et al, 2011 ; Duan et al, 2015 ). Impaired baroreflexive sensitivity in rats with hypertension or diabetes can be rescued by H 2 S treatment (Gu et al, 2013 ; El-Sayed et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%